Characteristics of Dysarthria in Post-Stroke Patients - Sofija Bajagić; Mile Vuković (Multidisciplinarni Pristupi u Edukaciji i Rehabilitaciji, 2025)
Dysarthria is a motor speech disorder caused by damage to the central nervous system. It is characterized by uncoordinated movements of the orofacial muscles. Several types of dysarthria can develop as a consequence of stroke, traumatic brain injury, and other neurological conditions. The aim of this study was to analyse the characteristics of dysarthria in patients who have suffered a stroke. The sample consisted of 30 patients undergoing rehabilitation at the Institute for Physical Medicine, Rehabilitation and Rheumatology, „Dr Simo Milošević“ in Igalo, Herceg Novi. The assessment tools used were the Screening Test for Dysarthria and the Test for Evaluation of Articulation. The results showed that stroke patients exhibited different types of dysarthria, with characteristics varying according to the site of nervous system damage. Speech in these patients was primarily characterized by disorders of articulation and phonation. Spastic dysarthria was the most common type observed.